2014
DOI: 10.1111/jocs.12276
|View full text |Cite
|
Sign up to set email alerts
|

Acute Aortic Insufficiency due to Rupture of an Aortic Valve Commissure

Abstract: Myxomatous degeneration generally involves the atrioventricular valves (mitral and tricuspid). Rarely, it may affect the aortic or pulmonary valve. We report a case of an acute severe aortic insufficiency due to a rupture of a commissure of the aortic valve in a patient who had previously undergone mitral valve surgery for myxomatous mitral valve prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Our case is one of the few cases reported in the literature. Pathologic examination confirmed myxoid degeneration which predisposed to cusp perforation [8]. Myxomatous degeneration macroscopically results in a thin region in each leaflet microscopically due to ongoing substitution of the collagen by mucopolysaccharides in the spongiosa leading to progressive weakness of the band [8].…”
Section: Discussionmentioning
confidence: 97%
“…Our case is one of the few cases reported in the literature. Pathologic examination confirmed myxoid degeneration which predisposed to cusp perforation [8]. Myxomatous degeneration macroscopically results in a thin region in each leaflet microscopically due to ongoing substitution of the collagen by mucopolysaccharides in the spongiosa leading to progressive weakness of the band [8].…”
Section: Discussionmentioning
confidence: 97%
“…However, in some cases, AR from blunt chest trauma can worsen gradually, taking patients up to 10 years or longer to become symptomatic [4]. It is reported that late-presenting patients may originally have had a small, clinically insignificant tear in one of the leaflets that gradually progressed with time as a result of hemodynamic stress [6]. Thus, it is important to confirm if a patient has a history of blunt chest trauma when they present with severe AR of unknown origin.…”
mentioning
confidence: 99%